2010
DOI: 10.1504/ijbet.2010.032695
|View full text |Cite
|
Sign up to set email alerts
|

Sleep staging from Heart Rate Variability: time-varying spectral features and Hidden Markov Models

Abstract: An alternative DSS which models the behaviour of the Heart Rate Variability (HRV) signal linked to stable (NREM) and instable (REM) cerebral waves during sleep and a probabilistic model of the sleep stages transitions for decision was developed. Time-Varying Autoregressive Models (TVAMs) were used as feature extractor while Hidden Markov Models (HMM) was used as time series classifier. 24 full polysomnography recordings from healthy sleepers were used for the analysis and those were separated in two sets of Sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
74
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(79 citation statements)
references
References 28 publications
4
74
1
Order By: Relevance
“…In that case it is clear that CRF achieves a higher accuracy and kappa for the 'regular' dataset, suggesting its superiority over LD for the same task, using the same base features. Regarding NREM detection, the CRF classifier achieves a comparable kappa and accuracy as the HMM classifier of Mendez et al [5] although they use a much smaller dataset limited to a narrow age range between 40 and 50 years. Regarding REM detection, CRF achieves a comparable kappa coefficient for the 'regular' dataset, and a lower coefficient for the 'all' dataset.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In that case it is clear that CRF achieves a higher accuracy and kappa for the 'regular' dataset, suggesting its superiority over LD for the same task, using the same base features. Regarding NREM detection, the CRF classifier achieves a comparable kappa and accuracy as the HMM classifier of Mendez et al [5] although they use a much smaller dataset limited to a narrow age range between 40 and 50 years. Regarding REM detection, CRF achieves a comparable kappa coefficient for the 'regular' dataset, and a lower coefficient for the 'all' dataset.…”
Section: Resultsmentioning
confidence: 99%
“…Cardiorespiratorybased sleep stage classification has been increasingly studied in recent years. Many studies have reported results on the classification of wake, REM, light sleep and deep sleep stages [2]- [4], detecting REM sleep [3], [5], [6], or differentiating light and deep sleep stages with an ambulatory device [3], [7]. The results in the literature are promising, but not yet at the level required for reliable sleep staging.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has established that it is possible to assess information about sleep stages using heart rate variability. [32][33][34] Knowledge about sleep stages is essential to estimate sleep quality and diagnose different sleep-related disorders. An important outlook of the ability to measure heart rate is the possibility to evaluate sleep stages using the proposed sleep monitor and therefore improve the diagnostic abilities in sleep monitoring significantly.…”
Section: Discussionmentioning
confidence: 99%
“…Virkkala et al have classified the sleep stages using only EOG signals with the agreement of 72% [16]. Mendez et al have utilized a Hidden Markov Model (HMM) with spectral features of heart rate variability to classify NREM and REM and the classification accuracy is measured around 80% in both training and test sets [17]. Liang et al have presented a rulebased sleep-stage classification method using features of temporal and spectral analyses of the EEG, EOG, and EMG signals with an agreement rate of 86.68% [18].…”
Section: Introductionmentioning
confidence: 99%